A Targeted "Capture" and "Removal" Scavenger toward Multiple Pollutants for Water Remediation based on Molecular Recognition. Issue 3 (10th December 2015) - Wang, Jie; Shen, Haijing; Hu, Xiaoxia; Li, Yan; Li, Zhihao; Xu, Jinfan; Song, Xiufeng; Zeng, Haibo; Yuan, Quan
Abstract : For the water remediation techniques based on adsorption, the long‐standing contradictories between selectivity and multiple adsorbability, as well as between affinity and recyclability, have put it on weak defense amid more and more severe environment crisis. Here, a pollutant‐targeting hydrogel scavenger is reported for water remediation with both high selectivity and multiple adsorbability for several pollutants, and with strong affinity and good recyclability through rationally integrating the advantages of multiple functional materials. In the scavenger, aptamers fold into binding pockets to accommodate the molecular structure of pollutants to afford perfect selectivity, and Janus nanoparticles with antibacterial function as well as anisotropic surfaces to immobilize multiple aptamers allow for simultaneously handling different kinds of pollutants. The scavenger exhibits high efficiencies in removing pollutants from water and it can be easily recycled for many times without significant loss of loading capacities. Moreover, the residual concentrations of each contaminant are well below the drinking water standards. Thermodynamic behavior of the adsorption process is investigated and the rate‐controlling process is determined. Furthermore, a point of use device is constructed and it displays high efficiency in removing pollutants from environmental water. The scavenger exhibits great promise to be applied in the next generation of water purification systems. Abstract : Ideal adsorbents are required for the next generation of water treatment . A highly efficient hybrid scavenger is rationally fabricated by combing the advantages of Janus nanoparticles, aptamers, and 3D porous structures in a stepwise manner. This scavenger can effectively remove heavy metals, organic pollutants, and pathogens simultaneously, bringing the promise of ideal adsorbents for water purification closer to fruition.